Diseño de un plan de marketing para la empresa odontored de la ciudad de Armenia, Quindío (2016)
The work is based on the design of a marketing plan aimed at the dental clinic Odontored, with the purpose of increasing its sales force and generates loyalty strategies for existing customers, considering that the vast majority of his patients have resorted to the acquisition of the services provided by it by that mode (voice to voice). some instruments and matrices be made to define which endogenous and exogenous factors that affect or provide opportunities to the company regarding the marketing area are, this in order to finalize the process with the implementation of strategies directly addressed the 4p (product- price-promotion-square). Keywords: marketing, customer loyalty, sales force, matrices, 4 p.